Morphology and Sequence Data of Mexican Populations of the Ciliate Parasite of Marine Fishes Trichodina rectuncinata (Ciliophora: Trichodinidae) - Islas Ortega, Alma G. (2018)
Trichodina rectuncinata is one of the trichodinids most widely distributed in marine fish. This ciliate species has been recorded in more than 20 host species belonging to 17 fish families worldwide. Previous comparative studies based on morphometric data revealed considerable morphological variation among specimens from different populations of T. rectuncinata. In this study, we conducted a morphometric- molecular analysis of three populations of T. rectuncinata to evaluate potential differences among 18S rRNA sequences, in relation to morphological variations. Smears were obtained from marine fishes in three localities along the Pacific coast of Mexico. Based on the shape of denticles, we found four different morphotypes for T. rectuncinata. This morphological variability does not correspond with the genetic divergence, suggesting that all analyzed populations belong to the same species. Further analyses using more variable markers are necessary to corroborate the findings of our study.